Demonstrations and price competition in new product release - Raphael Boleslavsky; Christopher Cotton; Haresh Gurnani (Queen's University, Department of Economics, 2015)
We incorporate product demonstrations into a game theoretic model of firm price competition. Demonstrations may include product samples, trials, return policies, reviews, or any other means by which a firm allows consumers to learn about their value for a new product. In our model, demonstrations help individual consumers learn whether they prefer an innovation over an established product. The innovative firm controls demonstration informativeness. When prices can respond to demonstration policies, the firm prefers to provide maximumly informative demonstrations, which optimally segment the market, dampen subsequent price competition, and maximize profits. In contrast, when prices are less flexible, the firm prefers only partially informative demonstrations, designed to maximize its market share at prevailing prices. Such a strategy can generate the monopoly profit for the innovative firm. We contrast the strategic role of demonstrations in our framework with the strategic role of capacity limits in models of judo economics (e.g. Gelman and Salop 1983), which also allow firms to divide a market and reduce competition.
Keywords: D83; L13; L15; 330; judo economics; demonstrations; product trials; product samples; return policies; money back guarantees; marketing strategy; product differentiation